Triggering Endogenous Cardiac Repair and Regeneration via Extracellular Vesicle-Mediated Communication - Bollini, Sveva; Smits, Anke M.; Balbi, Carolina; Lazzarini, Edoardo; Ameri, Pietro (Frontiers in Physiology, 2018)
A variety of paracrine signals create networks within the myocardium and mediate intercellular communications. Indeed, paracrine stimulation of the endogenous regenerative programme of the heart, mainly based on resident cardiac progenitor cell (CPC) activation together with cardiomyocyte proliferation, has become increasingly relevant for future cardiac medicine. In the last years, it has been shown that extracellular vesicles (EV), including exosomes (Ex), are powerful conveyors of relevant biological effects. EV have been proposed not only as promising therapeutic tool for triggering cardiac regeneration and improving repair, but also as means of better understanding the physiological and pathological relationships between specific cardiac components, including cardiomyocytes and fibroblasts. Actually, EV from different kinds of exogenous stem cells have been shown to mediate beneficial effects on the injured myocardium. Moreover, endogenous cells, like CPC can instruct cardiovascular cell types, including cardiomyocytes, while cardiac stromal cells, especially fibroblasts, secrete EV that modulate relevant aspects of cardiomyocyte biology, such as hypertrophy and electrophysiological properties. Finally, cardiomyocytes too may release EV influencing the function of other cardiac cell types. Therefore, EV-based crosstalk is thought to be important in both physiology and pathology, being involved in the responses of the heart to noxious stimuli. In this review we will discuss the role of EV in both regulating cardiac homeostasis and driving heart regeneration. In particular, we will address their role in: i) providing cardio-protection and enhancing cardiac repair mechanisms; ii) CPC biology and iii) influencing adult cardiomyocyte behaviour.